Salinity effects on the activities of ROS scavenging enzymes in leaves of two sweet potato clones - Mondal, S.; Burgert, S.; Asch, J.; Rahaman, E.H.M.S.; Asch, F. (Wiley, 2023)
Sweet potato production, particularly in coastal areas is often prone to salinity. Salt-tolerant clones will be needed to maintain production, but to date, little is known about salt tolerance traits in sweet potato. Salt stress may result in excessive uptake of unwanted ions into plant tissues leading to the formation of reactive oxygen species (ROS), which in turn may destroy membranes and reduce photosynthesis and growth. Antioxidant enzymes such as superoxide dismutase (SOD), peroxidase (POX), catalase (CAT), glutathione reductase (GR) and ascorbate peroxidase (APX) scavenge ROS and early changes in the activities of such enzymes could be used to identify salinity tolerant genotypes. Therefore, cuttings of two contrasting cultivars of sweet potato, BARI SP 8 (tolerant) and BARI SP 4 (sensitive) were greenhouse-cultivated in nutrient solution for 21 days and then exposed to 100 mmol NaCl for 7 days. Three, five and seven days after salt application the youngest leaves were sampled individually and enzyme activities, potassium (K) and sodium (Na) concentrations, and SPAD (as a proxy for chlorophyll content) were determined. In both varieties leaf growth was not affected by salinity and young leaves grown under salinity had higher SPAD values than older leaves. Na concentration increased over time, particularly in earlier and in older leaves, whereas K was reduced in younger leaves. In general, enzyme activities were strongly affected by leaf age and leaf position. SOD and APX showed varietal but no salinity effects, CAT increased under salinity in both varieties, whereas POX was strongly reduced and GR was strongly increased under salinity in BARI SP 8 with no effect in BARI SP 4. Enzyme activities were not correlated to leaf Na, neither in relation to leaf age, nor leaf number or duration of salt stress in both varieties. However, varietal differences were observed regarding leaf K. Activities of SOD were highly positive and of CAT highly negatively correlated with leaf K under salinity in BARI SP 8 but not in BARI SP 4, whereas activities of GR and POX were strongly positively correlated with leaf K in BARI SP 4 under salinity but not in BARI SP 8. We conclude that potassium may have a strong regulating role on leaf stress levels and therefore on the activities of antioxidant enzymes. Varieties may differ in their tolerance strategy and we have shown that salinity does not generally increase levels of ROS-scavenging enzymes in sweet potato leaves under salt stress. Confounding factors such as leaf age and leaf position as well as maintaining high leaf level K concentrations need to be considered when evaluating metabolic traits for salinity tolerance traits.